Pattern of Paediatric Neurological Disorders in Port Harcourt, Nigeria - Frank-Briggs, A. I. (Master Publishing Group, 2011)
BACKGROUND: Paediatric Neurological disorders in developing countries are very challenging. This is due to its chronicity, late presentation and unavailability of modern diagnostic facilities in developing countries like Nigeria. Lack of these modern technology and manpower contribute significantly to increased morbidity and mortality. This study demonstrates the pattern of neurological disorders and the challenges in management in a developing country. MATERIALS AND METHOD: This was a retrospective hospital based analysis of neurological disorders seen in the Paediatric neurology unit of the University of Port Harcourt Teaching hospital, Nigeria from January 2004 to December 2009. Descriptive statistics was used to present the result. RESULT: A total of 35,473 patients were seen in the Paediatric unit. Of these 2,379 had neurological disorders. This gave a prevalence of 6.7% of Paediatric neurological disorders. There were 1,431 males and 948 females (male: female ratio of 1.51:1.0). The age ranged from 3 months to 15 years. The age group 1->5 years accounted for the most affected age group constituting 87.7%. The most frequent Paediatric neurological disorders were epilepsy (24.6%), cerebral palsy (15.4%), and central nervous system infections (9.5%). CONCLUSIONS/RECOMMENDATION: Wide spectrum of neurological disorders occur in our environment. The high incidence of epilepsy and cerebral palsy suggests that effort should be geared towards educating the populace about early diagnosis and prompt management.